2017
DOI: 10.1097/igc.0000000000001022
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Space Invasion for Endometrial Cancer: Undertreatment and Overtreatment Risks

Abstract: Results suggest that LVSI remains a controversial issue in the management of patients with endometrial cancer. Acquiring a deeper knowledge and uniform criteria could avoid the risk of undertreatment and overtreatment in this group of patients with early-stage endometrial cancer. The identification of vascular pseudoinvasion is recommended, although the clinical and prognostic implications still need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Also, in this study, the degree of lymphovascular space invasion (LVSI) and myometrial invasion were found to adversely affect prognosis in patients diagnosed with endometrial cancer. Pulgar et al showed that the presence of LVSI was associated with reduced prognosis and a shorter survival rate [9]. Cusano et al analyzed the prognostic significance of LVSI in patients with (T1N0) node-negative surgically staged endometrial cancer, and showed that LVSI was an independent factor of risk for reduced overall survival (OS), as were age, histologic grade, and tumor stage [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this study, the degree of lymphovascular space invasion (LVSI) and myometrial invasion were found to adversely affect prognosis in patients diagnosed with endometrial cancer. Pulgar et al showed that the presence of LVSI was associated with reduced prognosis and a shorter survival rate [9]. Cusano et al analyzed the prognostic significance of LVSI in patients with (T1N0) node-negative surgically staged endometrial cancer, and showed that LVSI was an independent factor of risk for reduced overall survival (OS), as were age, histologic grade, and tumor stage [10].…”
Section: Discussionmentioning
confidence: 99%
“…Given the relative high incidence of distant recurrences for patients with lymphovascular invasion, even in the absence of lymph node metastasis, certain authors support the utilization of adjuvant chemotherapy since radiation therapy cannot eliminate microscopic metastases outside the radiation field. In a recent survey among active members of the Spanish Society of Gynecology and Obstetrics, 47% of responders recommend the addition of systemic chemotherapy for patients with early-stage endometrial cancer in the presence of lymphovascular invasion 19. Nevertheless, to date, data from randomized trials such as PORTEC-3 and GOG-249 do not support the utilization of adjuvant chemotherapy for early-stage endometrioid tumors, regardless of tumor grade and lymphovascular invasion status 18 20.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a survey of gynecologists, only half of the practitioners knew about vascular pseudoinvasion or how it occurs (13). The mechanism of vascular pseudoinvasion has been a matter of debate, as it probably results from adapting the technique, either intraoperatively or postoperatively.…”
Section: Discussionmentioning
confidence: 99%